Studies on the formation and synthetic mechanism of related substance G in potassium clavulanate production - Xiaoqing Jin; Guangxiang Cao; Xiaoxiao Zhang; Yuguo Chen; Liang Wang; Chuanqing Zhong (Universidade de São Paulo, 2015)
The objective of this study was to investigate the formation and synthetic mechanism of related substance G in potassium clavulanate production. The impurity in the potassium clavulanate final product, with a retention time of 13.5 min, was confirmed as related substance G by high performance liquid chromatography-mass spectrometry/mass spectrometry. Related substance G analysis during the production of clavulanic acid showed that this impurity could be synthesized during fermentation, and the amount increased with the fermentation time. Studies on its synthetic mechanism showed that L-tyrosine and succinic acid were the precursors for biosynthesis of related substance G in vivo. The reaction was deduced to be catalyzed by an enzyme. The enzyme was a type of extracellular enzyme present in the fermentation supernatant.